PREGNANCY PROBLEMS IN CHRONIC KIDNEY DISEASE (World Bulletin of Public Health, 2024)
While pregnancy among end-stage kidney disease patients is rare, the number of females becoming pregnant has been increasing worldwide during the last decade. Confirmatory data of this trend are found in the ANZDATA registry (Australian and New-Zealand Dialysis and Transplant registry), which showed an increase in pregnancy rates of women under hemodialysis over the years, from 0.67 per 1000 patients per year between 1986 and 1995 to 3.3 per 1000 between 1996 and 2024. PrThe aim of this review is to summarize the latest guidelines and practice points for ensuring the best outcome for both the fetus and the mother.
Keywords: pregnancy; kidney disease; hemodialysis